The Impact of Information Technology on Administrative Service Quality in Healthcare Institutions (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Healthcare institutions worldwide are undergoing digital transformation to improve efficiency and patient experiences. While many studies focus on clinical applications of information technology (IT), its impact on administrative service quality remains limited, even though administrative services are patients’ primary point of contact. This study examines how IT adoption influences administrative service quality in Indonesian healthcare institutions, focusing on relationships between IT implementation levels and service quality dimensions, as well as mediating and moderating factors. Using a mixed-methods sequential explanatory design, quantitative data were collected from 385 patients and 127 administrative staff across 24 hospitals, supported by 32 in-depth interviews. Service quality was measured using SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings show significant positive relationships between IT adoption and all service quality dimensions, with the strongest effects on reliability and responsiveness. Staff digital competency and system usability partially mediate these relationships, while implementation quality acts as a key moderating factor. Well-implemented systems yield substantially higher service improvements than poorly implemented ones. Most patients prefer digital services when functioning properly, although many report frustration when systems fail or staff lack competency. This study highlights the importance of effective IT implementation to enhance administrative service quality and offers practical insights for healthcare management.